2016
DOI: 10.3945/ajcn.115.121269
|View full text |Cite
|
Sign up to set email alerts
|

Plasma trimethylamine N-oxide concentration is associated with choline, phospholipids, and methyl metabolism

Abstract: High TMAO and choline concentrations are associated with an advanced cardiometabolic risk profile. Diabetes is related to higher plasma TMAO concentrations but also to alterations in interrelated pathways such as lipids, phospholipids, and methylation. Elevated plasma TMAO concentrations likely reflect a specific metabolic pattern characterized by low HDL and phospholipids in addition to hypomethylation. This trial was registered at clinicaltrials.gov as NCT02586181 and NCT02588898.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 42 publications
5
84
2
3
Order By: Relevance
“…Fasting plasma TMAO concentration in the supplemented group before starting the treatment and for the whole study period in the placebo group was similar to previously reported values in the same age and sex human subjects [23,24]. Since dietary carnitine is metabolized to TMAO in humans [25], L-carnitine supplementation induced tenfold increase in TMAO, observed in the midpoint of the study and maintained elevated until the end of the study.…”
Section: Discussion/conclusionsupporting
confidence: 88%
“…Fasting plasma TMAO concentration in the supplemented group before starting the treatment and for the whole study period in the placebo group was similar to previously reported values in the same age and sex human subjects [23,24]. Since dietary carnitine is metabolized to TMAO in humans [25], L-carnitine supplementation induced tenfold increase in TMAO, observed in the midpoint of the study and maintained elevated until the end of the study.…”
Section: Discussion/conclusionsupporting
confidence: 88%
“…Oxidative stress may impair betaine‐homocysteine methyltransferase, resulting in accumulation of circulating choline and betaine 38. Second, high plasma concentrations of choline and betaine have been associated with elevated concentrations of trimethylamine N‐oxide 39. This metabolite is related to microbiomic processing of dietary choline and to a lesser extent betaine, and systemic trimethylamine N‐oxide has been positively associated with adverse cardiovascular events 40.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective study indicated that higher intake of phosphatidylcholine, the precursor to the generation of TMAO, was independently associated with an increased risk of type 2 diabetes in 3 US populations (16). Previous studies have yielded inconsistent associations between plasma TMAO and type 2 diabetes (5,(17)(18)(19), and whether the association varies by FMO3 genetic variations has not yet been investigated. Our aim, therefore, was to determine the association of plasma TMAO with type 2 diabetes and to examine whether the association may be modified by a common FMO3 genetic variation in a casecontrol study.…”
Section: Introductionmentioning
confidence: 99%